Intrahepatic Cholestasis of Pregnancy Refractory to Multiple Medical Therapies and Plasmapheresis - Covach, Adam John; Rose, William Nicholas (American Journal of Perinatology Reports, 2017)
Objectives We report on a patient suffering from intractable itching secondary to intrahepatic cholestasis of pregnancy (ICP) unresponsive to conventional medical therapies. She was started on a regimen of therapeutic plasma exchange (TPE), which is often efficacious in relieving patient's itching from all causes of cholestasis, including ICP.Methods We performed a retrospective review of a patient's medical record.Results Following initial TPE, the patient reported dramatic relief of her itching and consequent insomnia. However, this effect was short lived, as subsequent TPE provided minimal relief, and may have actually worsened her itching. Out of concern for poor fetal outcomes, delivery was induced at 34 weeks gestational age. The child had an uncomplicated neonatal intensive care unit stay following delivery, and the mother reported > 90% relief of her symptoms 2 weeks after delivery.Conclusion TPE often provides longer term relief of itching because of ICP; however, it is not a panacea for these symptoms, and sometimes only delivery of the fetus can relieve maternal symptoms. In addition to the refractoriness to TPE, the case is also unusual for the early onset of ICP symptoms and the comorbidity of hepatitis C.
Keywords: intrahepatic cholestasis of pregnancy; plasmapheresis; bile acid; hepatitis C